Declines in social–emotional skills in college students during the COVID-19 pandemic - Cerutti, Janine; Burt, Keith B.; Moeller, Robert W.; Seehuus, Martin (Frontiers in Psychology, 2024)
Introduction The present study investigated whether social–emotional skills in first year college students differed before and after the coronavirus disease (COVID-19) lockdowns. Methods Participants (N = 1,685) consisted of first year college students (mean age 18.53 years) selected from a broader cohort enrolled in a longitudinal study on college mental health at liberal arts colleges in the United States. In a cohort-sequential design, participants completed an online survey assessing social–emotional skills in January of 2018, 2019, 2020, and 2022. Using analysis of covariance, we examined mean differences in social–emotional skills between students who were first years before (January 2018–2020) and after the lockdowns (January 2022), controlling for sociodemographic variables. Results The post-lockdown group scored significantly lower on emotional control and expressivity and marginally higher on social sensitivity compared to the pre-lockdown group. No group differences in social/emotional expressivity or social control were detected. Discussion These findings indicate that the COVID-19 lockdowns impaired some, but not all, social–emotional skills in first year college students. Addressing social–emotional skills in college may help to reduce the COVID-19 mental health burden.